High-entropy Prussian blue analogue positive electrode material, preparation method and application
By using the combination of potassium ferrocyanide and potassium citrate and the doping of manganese, iron, cobalt, nickel and copper in Prussian blue analog materials, the problems of instability of the material structure and many side reactions are solved, and the problem of instability of the material is achieved. The positive electrode material of sodium ion battery with high capacity and long life improves electrochemical performance.
Patent Information
- Application Number
- CN202411442938.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional Prussian blue analog materials have problems such as structural instability, many side reactions and poor cycle stability in the synthesis and electrochemical process, which limits their application in the positive electrode materials of sodium ion batteries.
By using potassium ferrocyanide and potassium citrate as precursors and chelators, combined with manganese, iron, cobalt, nickel and copper multi-doped metal elements, a high-entropy Prussian blue analog positive electrode material was prepared to increase the crystal gap space. Reduce the crystal water content and improve structural stability and conductivity.
The positive electrode material of sodium ion battery with high capacity, long life and low cost is achieved, reducing structural defects and side reactions in the electrochemical process, and improving the overall electrochemical performance of the material.
Smart Images

Figure CN119263305A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemistry, and in particular to a high-entropy Prussian blue analogue positive electrode material, a preparation method and an application thereof. Background Art
[0002] The invention belongs to the field of electrochemical technology, and specifically relates to a method for preparing a high-entropy Prussian blue analog positive electrode material with high capacity and high stability, using potassium ferrocyanide as a precursor and potassium citrate as a chelating agent to prepare crystals with larger interstitial spaces, while manganese, iron, cobalt, nickel, and copper are doped with metal elements in equal molar ratios to occupy redox sites. The material can be used as a high-specific energy and long-life positive electrode material for sodium ion batteries.
[0003] As the energy crisis and environmental pollution become increasingly serious, efficient energy storage technologies and systems are urgently needed to store and use new clean energy. Lithium-ion batteries are the current leaders in the smart electronic devices and electric markets, and have brought huge market advantages with their high energy density, long cycle life, high safety and green environmental protection. However, as an important component of lithium-ion batteries, lithium resource shortages, uneven distribution and steadily rising prices cannot meet the growing demand for large-scale energy storage. Therefore, some potential alternatives, such as sodium-ion batteries, are expected to become a new generation of energy storage systems.
[0004] Sodium resources are abundant in the earth's crust and are widely distributed and easy to extract. Because they are in the same main group of the periodic table as lithium, they have similar working principles. Most importantly, sodium-ion batteries have lower redox potentials than lithium-ion batteries. + In comparison, Na + With faster ion mobility and conductivity, sodium-ion batteries can use lightweight and cheap aluminum foil instead of copper foil as the current collector of electrode materials, which also reduces the cost of large-scale applications. Therefore, the development of high-performance sodium-ion batteries is of great significance to the realization of large-scale storage capacity systems with low cost, high voltage and high energy density.
[0005] The positive electrode of sodium-ion batteries limits the development of the entire battery system. In the process of searching for qualified positive electrode materials, people have found a variety of suitable compounds, including layered metal oxides, polyanionic compounds, and Prussian blue analogs. +The problems of low content, unstable Coulomb efficiency, severe phase change and high polarization voltage are plaguing the industry. Although polyanionic compounds are ideal cathode materials in terms of safety and thermal stability, their large molar mass leads to low energy density and specific capacity, which greatly limits the development of polyanionic compounds. Prussian blue analogues have an open framework structure with large ion channels and gaps in the lattice, so they are one of the few materials that can accommodate Na + , K + One of the host materials for larger alkali metal ions such as Na + Thanks to the rapid insertion and extraction of the three-dimensional open framework structure, Prussian blue analogues are expected to become the most ideal positive electrode material for sodium-ion batteries.
[0006] Prussian blue analog crystals are cubic structures composed of cyanide-bridged metal ions and are a coordination polymer. x P j [R k (CN)6] 1-y □ y ·zH2O (0≤x≤2, y<1) is the typical molecular formula of Prussian blue analogs, where A represents alkali metal or alkaline earth metal ions (Li, Na, K, etc.), P and R represent transition metal ions (Mn, Fe, Co, Ni, Cu, etc.), □ represents [R(CN)6] vacancies, and H2O represents interstitial / coordinated water molecules. In this crystal structure, the P ion coordinates with the N atoms on the six adjacent CN ligands, while the R ion coordinates with the C atoms on the adjacent CN ligands, thus forming a molecular structure with a rigid three-dimensional framework, which also has open ion channels and open interstitial spaces.
[0007] The research on Prussian blue analogues mainly focuses on hexacyanoferrate, mainly because its reaction potential is ≈1V (>SHE), and the preparation method is convenient and easy to synthesize, and it can be obtained by a simple water coprecipitation method. Prussian blue analogues are affected by their three-dimensional framework structure. The content of adsorbed water and crystal water during the synthesis and preparation process will affect their electrochemical properties, leading to more side reactions. Traditional Prussian blue analogues are usually formed by a transition metal (Mn, Fe, etc.) occupying the P site. Manganese-based Prussian blue analogues have the advantages of high capacity and high working voltage, but are limited by the Jahn-Teller effect and have unsatisfactory cycle stability; Iron-based Prussian blue analogues have higher capacity and working voltage, and the cycle stability is improved compared with manganese-based Prussian blue analogues, but their conductivity is poor, and the excessively high voltage platform makes the electrolyte easy to decompose and cannot exert all the electrochemical properties; Cobalt-based Prussian blue analogues have lower capacity and working voltage, good cycle stability, but high cost and poor overall performance; Nickel-based Prussian blue analogues have excellent cycle stability, but lower capacity and working voltage.
[0008] In the continuous study of traditional single transition metal Prussian blue analogs, it was found that although K + The radius of Na + (1.02 Å), but the Prussian blue analog cathode host [Fe(CN)6] is more susceptible to K + Therefore, using potassium as the base during preparation can increase the stability of the crystal structure and improve the cycle stability. At the same time, inspired by the new concept of "high entropy", that is, co-doping multiple elements in equal molar ratios to increase the configuration entropy, stabilize the crystal structure, produce mutual synergy, and improve the overall performance of the material. + The larger ionic radius, Mn 2+ and Fe 2+ High capacity, Co 2+ and Ni 2+ Excellent cycle stability, Cu 2+ The high conductivity not only makes the prepared material structure stable and has less crystal water, but also exhibits excellent electrochemical properties.
[0009] Therefore, the synthesis of crystals with larger interstitial spaces and the ability to allow manganese, iron, cobalt, nickel, and copper to occupy transition metal sites in equal molar ratios can produce high-entropy Prussian blue analogue cathode materials with high capacity and high stability, which are of great significance for promoting the development of high specific energy and long-life sodium-ion batteries. Summary of the invention
[0010] The purpose of the present invention is to overcome the above-mentioned problems generated in the synthesis and electrochemical processes of Prussian blue analogue materials, by synthesizing crystals with larger interstitial spaces, and at the same time making manganese, iron, cobalt, nickel, copper and other multi-doped metal elements occupy the redox sites in equal molar ratios, so as to produce a high-entropy Prussian blue analogue positive electrode material with high capacity and high stability, which has a simple process, low cost and can be mass-produced.
[0011] The technical solution of the present invention to solve the above problem is: + A larger ionic radius can increase the interstitial space of the crystal; Mn 2+ and Fe 2+ Provides high capacity for electrochemical processes; Co 2+ and Ni 2+ It plays a supporting role in the material structure, maintains structural integrity during structural evolution, and inhibits the occurrence of structural defects during the electrochemical process; Cu 2+ The three-dimensional structure improves the conductivity and accelerates the Na + The diffusion of ions is accelerated, and the kinetics of ion diffusion is promoted; the C6H5K3O7 chelating agent slows down the ion bonding rate and reduces the crystal water content.
[0012] The method for preparing the material comprises the following steps: (1) Prepare manganese source, iron source, cobalt source, nickel source and copper source solutions.
[0013] (2) Disperse the potassium ferrocyanide precursor and potassium citrate chelating agent in deionized water. After the dispersion is uniform, add a certain amount of manganese source, iron source, cobalt source, nickel source, and copper source solution. Stir continuously during the addition process until all the solutions are added.
[0014] (3) The mixed solution obtained in step (2) is washed by centrifugation using deionized water and anhydrous ethanol.
[0015] (4) Drying the colloid after centrifugal washing in step (3) in a vacuum drying oven.
[0016] (5) Grinding the solid particles obtained in step (4) into uniform powder to finally obtain high entropy Prussian blue analog positive electrode material particles.
[0017] According to the above scheme, the manganese source in step (1) includes one of manganese acetate, manganese chloride, manganese sulfate and manganese nitrate, the iron source includes one of ferrous acetate, ferrous chloride, ferrous sulfate and ferrous nitrate, the cobalt source includes one of cobalt acetate, cobalt chloride, cobalt sulfate and cobalt nitrate, the nickel source includes one of nickel acetate, nickel chloride, nickel sulfate and nickel nitrate, the copper source includes one of copper acetate, copper chloride, copper sulfate and copper nitrate, and the solvent of the manganese source, iron source, cobalt source, nickel source and copper source solution includes one of deionized water and ultrapure water.
[0018] According to the above scheme, the manganese source in step (1) is manganese sulfate, the iron source is ferrous sulfate, the cobalt source is cobalt sulfate, the nickel source is nickel sulfate, the copper source is copper sulfate, and the solvent of the manganese source, iron source, cobalt source, nickel source and copper source solution is deionized water.
[0019] According to the above scheme, the concentration of the manganese source solution in step (1) is in the range of 0.03~0.05 g / mL, the concentration of the iron source solution is in the range of 0.07~0.12 g / mL, the concentration of the cobalt source solution is in the range of 0.03~0.05 g / mL, the concentration of the nickel source solution is in the range of 0.03~0.05 g / mL, and the concentration of the copper source solution is in the range of 0.03~0.05 g / mL.
[0020] According to the above scheme, the potassium ferrocyanide precursor described in step (2) is K4[Fe(CN)6] yellow crystalline powder, and its mass volume ratio with deionized water is in the range of 1:3 to 1:6. The potassium citrate chelating agent is C6H5K3O7 white crystalline powder, and its mass ratio with the potassium ferrocyanide precursor is 1:1. The stirring speed is 400~500 r / min, and the duration is 1~2 h. The solvent of the precursor and chelating agent solution includes one of deionized water and ultrapure water. The molar ratio of manganese source, iron source, cobalt source, nickel source, copper source to potassium ferrocyanide in the mixed solution is 1:1, the stirring speed is 700~800 r / min, and the duration is 2~4h.
[0021] According to the above scheme, the deionized water and anhydrous ethanol are centrifuged and washed three times as described in step (3), and the centrifuge speed ranges from 8000 to 10000 r / min.
[0022] According to the above scheme, the drying temperature in step (4) is 120-150°C, and the drying time is 12-24 h.
[0023] According to the above scheme, the mixture is ground into a powder with uniform particles using a mortar as described in step (5).
[0024] Compared with the prior art, the invention has the following beneficial effects: The content of crystal water is reduced, and the side reactions of the electrochemical process are reduced.
[0025] The excessive crystal defects are improved, the structural stability is enhanced and the sodium ion diffusion barrier is reduced.
[0026] Taking into account high capacity, high rate and high stability, the assembled half-cell exhibits excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Other features, objectives and advantages of the present invention will become more apparent from a reading of the detailed description of non-limiting embodiments made with reference to the following accompanying drawings.
[0028] Figure 1 is the XRD diagram of the product of Example 2 of the present invention and the product of Comparative Example 1; Figure 2 TG diagram of the product of Example 2 of the present invention and the product of Comparative Example 1; Figure 3 is the XPS graph of Mn 2p of the product of Example 2 of the present invention; Figure 4 is the XPS graph of Fe 2p of the product of Example 2 of the present invention; Figure 5 : is the XPS graph of Co 2p of the product of Example 2 of the present invention; Figure 6 is the XPS graph of Ni 2p of the product of Example 2 of the present invention; Figure 7 : is the XPS graph of Cu 2p of the product of Example 2 of the present invention; Figure 8 This is a comparison chart of the rate performance of half-cells assembled with the positive electrode materials obtained in Example 2 of the present invention and Comparative Example 1 at different current densities; Fig. 9 is a charge and discharge curve diagram of the first cycle of a half-cell assembled with the positive electrode materials obtained in Example 2 of the present invention and Comparative Example 1 at a current density of 25 mA / g; Fig.10 1 is a comparison chart of the cycle performance of half-cells assembled with the positive electrode materials obtained in Example 2 of the present invention and in Comparative Example 1 after 200 cycles at a current density of 100 mA / g; Fig.11 This is a comparison chart of the cycle performance of half-cells assembled with the positive electrode materials obtained in Example 2 of the present invention and in Comparative Example 1 after 1000 cycles at a high current density of 1000 mA / g; Fig.12 It is a comparison diagram of electrochemical impedance of half-cells assembled with the positive electrode materials obtained in Example 2 of the present invention and in Comparative Example 1. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below by examples, which are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0030] A method for preparing a high entropy Prussian blue analogue positive electrode material comprises the following steps: (1) Prepare manganese source, iron source, cobalt source, nickel source and copper source solutions; (2) Dispersing the potassium ferrocyanide precursor and the potassium citrate chelating agent in deionized water, and adding a certain amount of manganese source, iron source, cobalt source, nickel source, and copper source solution after the dispersion is uniform, and stirring continuously during the addition process until all the solutions are added dropwise; (3) washing the mixed solution obtained in step (2) by centrifugation using deionized water and anhydrous ethanol; (4) drying the colloid after centrifugal washing in step (3) in a vacuum drying oven; (5) grinding the solid particles obtained in step (4) into a uniform powder to finally obtain high entropy Prussian blue analog positive electrode material particles; In step (1), the manganese source includes one of manganese acetate, manganese chloride, manganese sulfate, and manganese nitrate; the iron source includes one of ferrous acetate, ferrous chloride, ferrous sulfate, and ferrous nitrate; the cobalt source includes one of cobalt acetate, cobalt chloride, cobalt sulfate, and cobalt nitrate; the nickel source includes one of nickel acetate, nickel chloride, nickel sulfate, and nickel nitrate; the copper source includes one of copper acetate, copper chloride, copper sulfate, and copper nitrate; and the solvent of the manganese source, iron source, cobalt source, nickel source, and copper source solution includes one of deionized water and ultrapure water.
[0031] The method for preparing the high entropy Prussian blue analog positive electrode material, in step (1), the manganese source is manganese sulfate, the iron source is ferrous sulfate, the cobalt source is cobalt sulfate, the nickel source is nickel sulfate, the copper source is copper sulfate, and the solvent of the manganese source, iron source, cobalt source, nickel source, and copper source solution is deionized water.
[0032] The method for preparing the high entropy Prussian blue analog positive electrode material, in step (1), the concentration of the manganese source solution is in the range of 0.03-0.05 g / mL, the concentration of the iron source solution is in the range of 0.07-0.12 g / mL, the concentration of the cobalt source solution is in the range of 0.03-0.05 g / mL, the concentration of the nickel source solution is in the range of 0.03-0.05 g / mL, and the concentration of the copper source solution is in the range of 0.03-0.05 g / mL.
[0033] The method for preparing the high entropy Prussian blue analog positive electrode material, in step (2), the potassium ferrocyanide precursor is K4[Fe(CN)6] yellow crystalline powder, the mass volume ratio of which to deionized water is in the range of 1:3 to 1:6, the potassium citrate chelating agent is C6H5K3O7 white crystalline powder, the mass ratio of which to the potassium ferrocyanide precursor is 1:1, the stirring speed is 400-500 r / min, the duration is 1-2 h, the solvent of the precursor and chelating agent solution includes one of deionized water and ultrapure water; the molar ratio of the manganese source, iron source, cobalt source, nickel source, copper source to potassium ferrocyanide in the mixed solution is 1:1, the stirring speed is 700-800 r / min, and the duration is 2-4 h.
[0034] In the method for preparing the high entropy Prussian blue analogue positive electrode material, the drying temperature in step (4) is 120 to 150° C. and the drying time is 12 to 24 h.
[0035] The high entropy Prussian blue analog positive electrode material preparation method, the high entropy Prussian blue analog positive electrode material, uses potassium ferrocyanide as a precursor and potassium citrate as a chelating agent to prepare crystals with larger interstitial spaces, and at the same time allows manganese, iron, cobalt, nickel, copper and other multi-doped metal elements to occupy redox sites in equal molar ratios.
[0036] The high entropy Prussian blue analogue positive electrode material is prepared by any of the preparation methods described above.
[0037] The application of the high entropy Prussian blue analog positive electrode material is its application as a positive electrode material for sodium ion batteries.
[0038] The present invention provides a method of using a solution containing a manganese source, an iron source, a cobalt source, a nickel source and a copper source as a dopant, bonding the five elements with potassium ferrocyanide by a water coprecipitation method, and then obtaining a high-entropy Prussian blue analogue positive electrode material through processes such as centrifugal washing and vacuum drying.
[0039] Example 1 A method for preparing a high entropy Prussian blue analog sodium ion battery positive electrode material comprises the following steps: (1) Dissolve 1.510 g of manganese sulfate, 1.519 g of ferrous sulfate, 1.549 g of cobalt sulfate, 1.547 g of nickel sulfate, and 1.596 g of copper sulfate in 50 ml of deionized water, respectively, and stir at 450 r / min for 90 min by magnetic stirring, which are called manganese source, iron source, cobalt source, nickel source, and copper source solutions, respectively. The concentration of the manganese source solution is 0.0302 g / mL, the concentration of the iron source solution is 0.0304 g / mL, the concentration of the cobalt source solution is 0.0304 g / mL, the concentration of the nickel source solution is 0.0310 g / mL, and the concentration of the copper source solution is 0.0319 g / mL.
[0040] (2) Disperse 18.417 g of K4[Fe(CN)6] precursor and 15.319 g of C6H5K3O7 chelating agent evenly in 100 ml of deionized water and stir at 450 r / min for 90 min by magnetic stirring. Add 50 ml of manganese source, iron source, cobalt source, nickel source and copper source solution to the solution at the same time. Adding 50 ml of manganese source, iron source, cobalt source, nickel source and copper source solution represents a doping amount of 20% for each of the five elements, and then stir at 800 r / min for 2 h at room temperature until all the solutions are added.
[0041] (3) Allow the mixed solution in (2) to stand for 12 hours, discard the supernatant, and place the remaining solution in centrifuge tubes and wash them three times by centrifugation using deionized water and anhydrous ethanol at a speed of 10,000 r / min.
[0042] (4) Place the colloid after centrifugal washing in (3) in a vacuum drying oven at a drying temperature of 150°C for 24 h.
[0043] (5) The solid particles dried in (4) are ground into a powder with uniform particles using a mortar to finally obtain high entropy Prussian blue analog positive electrode material particles.
[0044] Example 2 A method for preparing a high entropy Prussian blue analog sodium ion battery positive electrode material comprises the following steps: (1) Dissolve 1.887 g of manganese sulfate, 1.898 g of ferrous sulfate, 1.937 g of cobalt sulfate, 1.934 g of nickel sulfate, and 1.995 g of copper sulfate in 50 ml of deionized water, respectively, and stir at 450 r / min for 90 min by magnetic stirring, which are called manganese source, iron source, cobalt source, nickel source, and copper source solutions, respectively. The concentration of the manganese source solution is 0.0378 g / mL, the concentration of the iron source solution is 0.0380 g / mL, the concentration of the cobalt source solution is 0.0387 g / mL, the concentration of the nickel source solution is 0.0387 g / mL, and the concentration of the copper source solution is 0.0399 g / mL.
[0045] (2) Disperse 23.021 g of K4[Fe(CN)6] precursor and 19.149 g of C6H5K3O7 chelating agent evenly in 100 ml of deionized water and stir at 450 r / min for 90 min by magnetic stirring. Add 50 ml of manganese source, iron source, cobalt source, nickel source and copper source solution to the solution at the same time. Adding 50 ml of manganese source, iron source, cobalt source, nickel source and copper source solution represents a doping amount of 20% for each of the five elements, and then stir at 800 r / min for 2 h at room temperature until all the solutions are added.
[0046] (3) Allow the mixed solution in (2) to stand for 12 hours, discard the supernatant, and place the remaining solution in centrifuge tubes and wash them three times by centrifugation using deionized water and anhydrous ethanol at a speed of 10,000 r / min.
[0047] (4) Place the colloid after centrifugal washing in (3) in a vacuum drying oven at a drying temperature of 150°C for 24 h.
[0048] (5) The solid particles dried in (4) are ground into a powder with uniform particles using a mortar to finally obtain high entropy Prussian blue analog positive electrode material particles (hereinafter referred to as HE-K-PBA).
[0049] Example 3 A method for preparing a high entropy Prussian blue analog sodium ion battery positive electrode material comprises the following steps: (1) Dissolve 2.265 g of manganese sulfate, 2.278 g of ferrous sulfate, 2.324 g of cobalt sulfate, 2.321 g of nickel sulfate, and 2.394 g of copper sulfate in 50 ml of deionized water, respectively, and stir at 450 r / min for 90 min by magnetic stirring, which are called manganese source, iron source, cobalt source, nickel source, and copper source solutions, respectively. The concentration of the manganese source solution is 0.0453 g / mL, the concentration of the iron source solution is 0.0456 g / mL, the concentration of the cobalt source solution is 0.0465 g / mL, the concentration of the nickel source solution is 0.0464 g / mL, and the concentration of the copper source solution is 0.0479 g / mL.
[0050] (2) Disperse 27.625 g of K4[Fe(CN)6] precursor and 22.979 g of C6H5K3O7 chelating agent evenly in 100 ml of deionized water and stir at 450 r / min for 90 min by magnetic stirring. Add 50 ml of manganese source, iron source, cobalt source, nickel source and copper source solution to the solution at the same time. Adding 50 ml of manganese source, iron source, cobalt source, nickel source and copper source solution represents a doping amount of 20% for each of the five elements, and then stir at 800 r / min for 2 h at room temperature until all the solutions are added.
[0051] (3) Allow the mixed solution in (2) to stand for 12 hours, discard the supernatant, and place the remaining solution in centrifuge tubes and wash them three times by centrifugation using deionized water and anhydrous ethanol at a speed of 10,000 r / min.
[0052] (4) Place the colloid after centrifugal washing in (3) in a vacuum drying oven at a drying temperature of 150°C for 24 h.
[0053] (5) The solid particles dried in (4) are ground into a powder with uniform particles using a mortar to finally obtain high entropy Prussian blue analog positive electrode material particles.
[0054] Preparation and assembly process of electrode materials: The prepared high entropy Prussian blue analog positive electrode material, Super P, and PVDF were mixed and ground in a mass ratio of 7:2:1 and dispersed in an appropriate amount of 1-methyl-2-pyrrolidone. A multi-sample tissue grinder was used at a vibration frequency of 50-70 Hz / s. After 8-10 min of vibration, a uniform slurry was formed. Then, a scraper was used to evenly coat it on aluminum foil, and it was heated and dried at 150°C in a vacuum drying oven for 12 h to obtain the positive electrode material. The electrode sheet was made by cutting the aluminum foil into electrode discs with a diameter of 10 mm. The mass loading of the active material of the cut electrode sheet was 2.0-3.0 mg / cm 2Sodium metal was used as the negative electrode with a diameter of 14 mm, Whatman D series glass fiber paper was used as the battery separator, 1 mol / L NaClO4 was dissolved in dimethyl carbonate (DMC), ethylene carbonate (EC), ethyl methyl carbonate (PC) with a volume ratio of 1:1:1, and 5% mass fraction of fluoroethylene carbonate (FEC) was added as the electrolyte, and a CR2016 button cell was assembled in an argon atmosphere glove box, and the electrochemical performance of the battery was tested (2.0-4.2V).
[0055] The XRD pattern of the HE-K-PBA product prepared in Example 2 is as follows Figure 1 As shown in Figure 2, the XRD image shows that HE-K-PBA is a single-phase cubic Prussian blue analog material, does not contain any impurities, and belongs to the F-43m space group (ICDD No. 01-075-0038). The material prepared in Example 2 has high crystallinity, which is conducive to the deintercalation of sodium ions. The XPS image of the HE-K-PBA product prepared in this Example 2 is shown in Figure 2. Figure 4 , 5 As shown in Figures 6, 7, and 8, it is shown that the five elements Mn, Fe, Co, Ni, and Cu were successfully doped into the material.
[0056] The first cycle charge and discharge curve of the button cell assembled with the HE-K-PBA electrode material and sodium metal prepared in Example 2 at a current of 25 mA / g is as follows: Fig. 9 As shown in Figure 2, the discharge capacity is as high as 124.9 mAh / g, and the coulombic efficiency is as high as 96.6%, which proves that it has excellent charge and discharge capabilities. The rate performance of the button cell assembled with the HE-K-PBA electrode material prepared in Example 2 and sodium metal at different current densities is shown in Figure 2. Fig. 9 As shown in the graph, when the current density gradually increases from 25 mA / g to 50, 100, 200, 300, 500, 800, 1000 and then back to 100 mA / g, the specific capacities are 120.8, 112.8, 104.3, 94.1, 89.2, 83.5, 77.6, 75.0, 99.8 mAh / g, respectively, showing that it has excellent rate performance. The cycle performance of the button cell assembled with the HE-K-PBA electrode material prepared in Example 2 at a current density of 100 mA / g is shown in the graph. Fig.10 As shown in the graph, after 200 cycles, it still has a specific capacity of 81.8 mAh / g, and the capacity retention rate is 89.0%, proving that it has excellent cycle stability. The cycle performance of the button cell assembled with the HE-K-PBA electrode material prepared in Example 2 and sodium metal at a high current density (1000 mA / g) is shown in the graph. Fig.11As shown in the figure, after 1000 cycles, it still has a specific capacity of 59.27 mAh / g, and the capacity retention rate is 82.7%, proving its excellent high current cycling performance. The electrochemical impedance diagram of the button cell assembled with the HE-K-PBA electrode material prepared in Example 2 and sodium metal is shown in the figure. Fig.12 As shown, it indicates that its charge transfer impedance is low and the degree of polarization is small, which is beneficial to improving the charging and discharging capacity.
[0057] Comparative Example 1 The difference between Comparative Example 1 and Examples 1-3 is that a Prussian blue analogue positive electrode material (Mn-K-PBA) doped with only manganese element is used as a comparative example.
[0058] The battery assembly test process is consistent with Examples 1-3. The XRD pattern of the Mn-K-PBA product prepared in Comparative Example 1 is shown in Figure 1 As shown, the XRD pattern indicates that Mn-K-PBA is a single-phase cubic Prussian blue analog material without any impurities and belongs to the F-43m space group (ICDD No.00-051-1896).
[0059] The first cycle charge and discharge curve of the button cell assembled with the Mn-K-PBA electrode material and sodium metal prepared in this comparative example 1 at a current of 25 mA / g is as follows: Fig. 9 As shown in Figure 1, its discharge specific capacity is low and its coulombic efficiency is low, indicating that its charge and discharge capacity is poor. The rate performance of the button cell assembled with the Mn-K-PBA electrode material prepared in this comparative example 1 at different current densities is shown in Figure 1. Fig. 9 As shown in the graph, when the current density gradually increases from 25 mA / g to 100, 200, 300, 500, 800, 1000 and then back to 100 mA / g, the specific capacities are 107.7, 91.2, 80.4, 55.9, 40.0, 23.8, 15.0, and 77.4 mAh / g, respectively, showing extremely poor rate performance. The cycle performance of the button cell assembled with the Mn-K-PBA electrode material prepared in this comparative example 1 at a current density of 100 mA / g is shown in the graph. Fig.10 As shown in FIG. 1 , the capacity retention rate rapidly decays to 73.48% after 200 cycles, indicating that its cycle performance is poor. The cycle performance of the button cell assembled with the Mn-K-PBA electrode material prepared in this comparative example 1 and sodium metal at a high current density (1000 mA / g) is shown in FIG. Fig.11 As shown in Figure 1, its specific capacity is only 14.25 mAh / g, and the capacity retention rate decays to 97% after 1000 cycles, further indicating its poor cycle stability. The electrochemical impedance diagram of the button cell assembled with the Mn-K-PBA electrode material prepared in this comparative example 1 and sodium metal is shown in Figure 11. Fig.12 As shown, it exhibits a large charge transfer impedance and severe polarization phenomenon.
[0060] In summary, the preparation process of the high entropy Prussian blue analogue positive electrode material HE-K-PBA doped with manganese, iron, cobalt, nickel and copper is simple, low cost and can be mass-produced. The prepared high entropy Prussian blue analogue positive electrode material HE-K-PBA has larger interstitial space, lower crystal water content and fewer structural defects, which can promote the diffusion capacity of sodium ions and enhance structural stability. It is one of the candidates for the next generation of high specific energy, fast charging and long life sodium ion battery positive electrode materials.
Claims
1. A method for preparing a high entropy Prussian blue analogue positive electrode material, characterized in that: The following steps are included: (1) Prepare manganese source, iron source, cobalt source, nickel source and copper source solutions; (2) Dispersing the potassium ferrocyanide precursor and the potassium citrate chelating agent in deionized water, and adding a certain amount of manganese source, iron source, cobalt source, nickel source, and copper source solution after the dispersion is uniform, and stirring continuously during the addition process until all the solutions are added dropwise; (3) washing the mixed solution obtained in step (2) by centrifugation using deionized water and anhydrous ethanol; (4) drying the colloid after centrifugal washing in step (3) in a vacuum drying oven; (5) grinding the solid particles obtained in step (4) into a uniform powder to finally obtain high entropy Prussian blue analog positive electrode material particles; In step (1), the manganese source includes one of manganese acetate, manganese chloride, manganese sulfate, and manganese nitrate; the iron source includes one of ferrous acetate, ferrous chloride, ferrous sulfate, and ferrous nitrate; the cobalt source includes one of cobalt acetate, cobalt chloride, cobalt sulfate, and cobalt nitrate; the nickel source includes one of nickel acetate, nickel chloride, nickel sulfate, and nickel nitrate; the copper source includes one of copper acetate, copper chloride, copper sulfate, and copper nitrate; and the solvent of the manganese source, iron source, cobalt source, nickel source, and copper source solution includes one of deionized water and ultrapure water.
2. The method for preparing the high entropy Prussian blue analogue cathode material according to claim 1, characterized in that: In step (1), the manganese source is manganese sulfate, the iron source is ferrous sulfate, the cobalt source is cobalt sulfate, the nickel source is nickel sulfate, the copper source is copper sulfate, and the solvent of the solutions of the manganese source, iron source, cobalt source, nickel source and copper source is deionized water.
3. The method for preparing the high entropy Prussian blue analogue cathode material according to claim 1, characterized in that: In step (1), the concentration of the manganese source solution is in the range of 0.03-0.05 g / mL, the concentration of the iron source solution is in the range of 0.07-0.12 g / mL, the concentration of the cobalt source solution is in the range of 0.03-0.05 g / mL, the concentration of the nickel source solution is in the range of 0.03-0.05 g / mL, and the concentration of the copper source solution is in the range of 0.03-0.05 g / mL.
4. The method for preparing the high entropy Prussian blue analogue cathode material according to claim 1, characterized in that: In step (2), the potassium ferrocyanide precursor is K4[Fe(CN)6] yellow crystalline powder, and the mass volume ratio of the potassium ferrocyanide precursor to deionized water is in the range of 1:3 to 1:
6. The potassium citrate chelating agent is C6H5K3O7 white crystalline powder, and the mass volume ratio of the potassium ferrocyanide precursor to the potassium ferrocyanide precursor is 1:
1. The stirring speed is 400-500 r / min, and the duration is 1-2 h. The solvent of the precursor and chelating agent solution includes one of deionized water and ultrapure water. The molar ratio of the manganese source, iron source, cobalt source, nickel source, copper source to potassium ferrocyanide in the mixed solution is 1:
1. The stirring speed is 700-800 r / min, and the duration is 2-4 h.
5. The method for preparing the high entropy Prussian blue analogue cathode material according to claim 1, characterized in that: In step (4), the drying temperature is 120-150° C. and the drying time is 12-24 h.
6. The method for preparing the high entropy Prussian blue analogue cathode material according to claim 1, characterized in that: The high-entropy Prussian blue analog positive electrode material uses potassium ferrocyanide as a precursor and potassium citrate as a chelating agent to prepare crystals with larger interstitial spaces, while allowing manganese, iron, cobalt, nickel, and copper to be doped with multiple metal elements in equal molar ratios to occupy redox sites.
7. A high entropy Prussian blue analogue cathode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. The use of the high entropy Prussian blue analogue cathode material as claimed in claim 7, characterized in that: Its application as positive electrode material for sodium ion batteries.
Citation Information
Cited By
Prussian blue analogue electrode and preparation method and application thereof
CN120097469A
High-entropy Prussian blue analogue composite MXene electrode material and preparation method and application thereof
CN120423652A
High-entropy solid energy storage material and preparation method and application thereof
CN121591230A
High-entropy solid energy storage material, preparation method and application thereof
CN121591230B